2016
DOI: 10.17261/pressacademia.2016116555
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of mobile payment systems: a study on mobile wallets

Abstract: Few years back mobile wallet was something majority in India did not hear about but its use saw a huge leap in last couple of years with the surge of smart phones, high speed internet connectivity using 3G and 4G and the lucrative offers mobile wallets provide. This research paper is an attempt to study the preference towards mobile wallet among the students studying in various universities in Lucknow city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 54 publications
6
64
0
7
Order By: Relevance
“…Mobile payment is defined as a payment which is made by the users through their wireless devices such as smartphones (Bezhovski, 2016). Similarly, mobile payment is acknowledged as the situation of taking advantage from information and communication technologies and making payments of products and services through mobile devices of users (Aydin & Burnaz, 2016). Recent development of technologies related to mobile payment introduces digital money, digital receipts, and digital coupons, bringing more flexibility in mobile payment (Doan, 2014;Husson, 2015).…”
Section: Literature Surveymentioning
confidence: 99%
“…Mobile payment is defined as a payment which is made by the users through their wireless devices such as smartphones (Bezhovski, 2016). Similarly, mobile payment is acknowledged as the situation of taking advantage from information and communication technologies and making payments of products and services through mobile devices of users (Aydin & Burnaz, 2016). Recent development of technologies related to mobile payment introduces digital money, digital receipts, and digital coupons, bringing more flexibility in mobile payment (Doan, 2014;Husson, 2015).…”
Section: Literature Surveymentioning
confidence: 99%
“…Additionally, [44] stated that the more an individual"s observation about the system as being easy to use, the more expected the individual develops a positive attitude towards using it. The relationship between PEOU and attitude has been hypothesized and endorsed by various studies [39], [40], [45], [46]. Hereafter, the hypothesis is developed that:  H3; Perceived ease of use significantly affect consumers attitude toward using mobile banking.…”
Section: Perceived Ease Of Use (Peou)mentioning
confidence: 99%
“…Attitude is "the degree of individual"s positive or negative evaluation or appraisal of the behaviour in question" [46] whereas, behavioural intention is the measure of the probability of an individual using the application/system [61]. consumers intention of using new technology is fully dependent on his/her attitude [18].…”
Section: G Attitude As a Mediator And Dependent Variable Behaviouralmentioning
confidence: 99%
“…Primary data analysis applying stratified random sampling among two distinct groups (users and non-users) and analyzed using partial least squares structural equation modelling. The study revealed the challenges, an organization faced to sustain in this market [1]. Shailendra Singh Rana studied on the preferences towards mobile wallet by developing of smart phones and high-speed internet connectivity using 3G and 4G [11].…”
Section: Review Literaturementioning
confidence: 99%